Linking motor-related brain potentials and velocity profiles in multi-joint arm reaching movements - Amengual, Julià L.; Marco-Pallarés, Josep; Grau, Carles; Münte, Thomas F.; Rodríguez-Fornells, Antoni (Frontiers in Human Neuroscience, 2014)
The study of the movement related brain potentials (MRPBs) needs accurate technical approaches to disentangle the specific patterns of bran activity during the preparation and execution of movements. During the last forty years, synchronizing the electromiographic activation (EMG) of the muscle with the electrophysiological recordings (EEG) has been commonly ussed for these purposes. However, new clinical approaches in the study of motor diseases and rehabilitation suggest the demand of new paradigms that might go further into the study of the brain activity associated with the kinematics of movement. As a response to this call, we have used a 3-D hand tracking system with the aim to record continuously the position of an ultrasonic sender located on the hand during the performance of multi-joint self-pace movements. We synchronized the time-series of position of velocity of the sender with the EEG recordings, obtaining specific patterns of brain activity as a function of the fluctuations of the kinematics during the natural movement performance. Additionally, the distribution of the brain activity during the preparation and execution phases of movement was similar that reported previously using the EMG, suggesting the validity of our technique. We claim that this paradigm could be usable in patients because of its simplicity and the potential knowledge that can be extracted from clinical protocols.